Formas de negação não canônicas nas construções [NEM X], [NEM EM], [NEM QUE] e [NEM SE] - ARAÚJO, Irna Moraes (2025)
Riassunto; Alemão: Zusammenfassung; Resumo Indígena. Fonte: PDF The current work guides a discussion about the phenomenon of denial, whose object are the constructions [Nem X], [Nem em], [Nem que] e [Nem se], which have an element that belongs to the set of canonical forms. This study has the objective to show the process of linguistic adaptation that occurs in Portuguese, through a look related to language motivation. For this reason, this research is justified by the verification that human beings are expressive, through the most varied ways of communicating. This work aims to complement existing studies in the Functionalism field, since the language is functional and dynamic, and is always in constant evolution. Therefore, it is essential to execute researches related to linguistics variations among which can be mentioned the object of this study, and the forms they occur, considering that these alterations exist daily and are essential to carry out communication in language.